Synthesis and Polymerization of 4-Vinylbenzylphenylsulfone - Abu-Abdoun, Ideisan I. (Journal of Research Updates in Polymer Science, 2023)
The preparation of new sulfone monomer and polymer based on 4-Vinylbenzylphenylsulfone (4-VBPS) and free radical polymerization was investigated, based on the reaction of chloromethyl styrene with sodium phenyl sulfone (phSO2Na) in dimethylformamide (DMF), using the phase transfer catalysts 18-crown-6. Copolymerization of the prepared sulphone monomer with p-methylstyrene was carried out at 65 ˚C. Nonpolymerizable 4-Ethylbenzylphenylsulfone was also prepared. The prepared monomers and polymers were characterized by different spectroscopic techniques, the number-average molecular weights (Mn) of the resulting polymer was found to be in the range of 70,100 -73,100, with polydispersity indices (Mw/Mn) vary from 1.8 to 1.9. Photolysis of the prepared polysulfone polymer and possible grafting of methyl methacrylate (MMA) monomer will be reported.